Rancang Bangun Perangkat Belajar Braille Elektronik Berbasis Raspberry Pi - Hidayat hidayat; Muhammad Yusuf (Ultima Computing : Jurnal Sistem Komputer, 2020)
The aim of the present research was to design and implement a braille electronic learning device for helping children who are blind in studying. The method used was an experimental method that includes the study of literature, the design process, the process of implementing tool manufacturing and also functional testing. This is made easier for blind people to learn to arrange words, translate words. The system designed consists of the Raspberry Pi as the main data processor, six push-buttons as input for braille codes, five push-buttons as control buttons, external MMC memory as a storage place for the operating system documents used by Raspberry Pi and also as a storage place for digital information such as applications that are made and also voices and the speaker functions as voice output, and also the LCD functions to display letters or numbers entered by users, it is only intended for teachers or instructors who can see when accompanying blind students. The overall system test results produce the expected output, which can speak words or numbers and translate words in two languages (Bahasa-English) correctly.